The ideal packaging system for ’Santa Clara’ tomato transportation - Alves Luengo, Rita de Fátima; Furuya, Tadashi; Oliveira da Silva, José Luiz (Pesquisa Agropecuaria Brasileira, 1997)
The purpose of this paper was to measure the effect of wooden and plastic boxes, with or without rubber and foam rubber shock absorbers, on hardness and mechanical injuries of tomato fruits. Treatments were: wooden box, wooden box with external rubber, wooden box with internal foam rubber (density 16 and 20 mm thickness), plastic box, plastic box with external rubber, plastic box with internal foam rubber (density 16 and 20 mm thickness). Statistical design was entirely randomized with four repetitions. Each repetition had 30 tomato fruits marked and disposed in the central portion of the box, complemented with other tomato fruits. Tomato fruits were transported on a rough road, with average speed of 56.2 km/h and maximum speed of 90 km/h, in a distance of 50 km. The conclusion was that plastic boxes are better than wooden boxes for tomato transportation, because of smaller number of mechanical injuries in the fruits. Rubber and foam rubber protected fruits from undesirable effects of transportation, with superiority of foam rubber as a shock absorber.